PARTISIPASI PETANI DALAM PROGRAM SERIBU HEKTAR SISTEM TANAM PADI JAJAR LEGOWO DI KECAMATAN KARANGPANDAN KABUPATEN KARANGANYAR - Nisa Munfa'ati; Eny Lestari; Arip Wijianto (Universitas Sebelas Maret, 2017)
This aims of this research to examine the level of farmers participation, to examine the socio-economic factors of farmers, and to examine the relationship between socio-economic factors of farmers with the level of farmer participation in one thousands hectareprogram of jajar legoworice planting system. The research location was determined purposively in KarangpandanSubdistrict ofKaranganyar Regency with the consideration that KarangpandanSubdistrict is one of program implementer that having the lowest production income compared to other subdistrict in Karanganyar Regency. Sampling was conducted using proportional random sampling method as many as 60 respondents. Methods of data analysis using interval width formula, scoring calculations on Likert scale and Rank Spearman correlation analysis method (RS). The results showed that: the participation of farmers in one thousands hectareprogram of jajar legoworice planting system are: the planning stage, the implementation stage, the evaluation stage is high. The socio-economic factors of farmers are: the age, theformal education, the non-formal education, the land tenure, the income, and thesocial environment is high. There is a very significant correlationbetween the formal education, non-formal education, income, and the social environment; There is a significant correlation to the area of land tenure; and there is no significant correlation on the age of respondents with farmer participation level in one thousands hectareprogram of jajar legoworice planting system.